Implikasi Pendidikan dari QS Ali-Imran 133- 135 tentang Ciri-Ciri Orang Yang Bertaqwa - Rizal Hermawan; Eko Surbiantoro (UPT Publikasi Ilmiah Unisba, 2024)
Abstract. This research focuses on studying Q.S Ali-Imran verses 133-135 regarding the characteristics of people who are devoted to morals towards fellow humans. The focus of this research includes 1) What is the content of the Al-Qur'an Surah Ali-Imran verses 133-135 according to the commentator? 2) What are the views of education experts regarding morals towards fellow humans? 3) What is the essence of the Koran, Surah Ali-Imran verses 133-135? 4) What are the implications of education in Al-Qur'an Surah Ali-Imran verses 133-135 regarding the characteristics of people who are devoted to morals towards fellow humans? In this research the author uses the library research method and is included in the qualitative-descriptive research type and in interpreting the Al-Qur'an uses the tahlili interpretation method. Library research. As a result of this research, the writer concludes that the educational implications contained in Q.S Ali-Imran verses 133-135. Abstrak. Penelitian ini berfokus untuk mengkaji Q.S Ali-Imran ayat 133-135 mengenai ciri-ciri orang yang bertaqwa terhadap akhlak kepada sesama manusia. Fokus penelitian ini meliputi 1)Apa isi kandungan dari al-Qur’an surat ali-Imran ayat 133-135 menurut mufasir? 2) Bagaimana pandangan ahli pendidikan mengenai akhlak kepada sesama manusia? 3) Apa esensi dari al-Qur’an surat ali-Imran ayat 133-135 menurut? 4) Bagaimana implikasi pendidikan dalam al-Qur’an surat ali- Imran ayat 133-135 tentang ciri-ciri orang yang bertaqwa terhadap akhlak kepada sesama manusia?. Dalam penelitian ini penulis memakai metode library research dan termasuk dalam jenis penelitian kualitatif-deskriptif serta dalam menafsirkan Al-Qur’an menggunakan metode tafsir tahlili. Library research. Hasil dari penelitian ini penulisan mengambil kesimpulan bahwa implikasi pendidikan yang terkandung dalam Q.S Ali-Imran ayat 133-135.